Woven World: Neotraditional Symbols of Unity in Vanuatu - Keller, Janet D. (The Australian journal of anthropology, 1988)
The importance of kastom to national identity in Vanuatu has been recognized. In this paper I identify plaiting technology in general and basketry in particular — which once served to distinguish ethnic groups in Vanuatu — as emerging symbols of ni-Vanuatu unity. I argue that unlike these kastom traditions often discussed in the literature, plaiting and basketry need not be reinvented. Plaiting is a customary practice which has rich contemporaneous expressions. Plaited products may be fully elaborated in local detail and yet, as shared productions of a technology with common features, can simultaneously represent ni-Vanuatu identity.